Il problema biogiuridico della libertà di cura e la metafisica della pandemia (Società e diritti, 2021)
AbstractThe article examines the pandemic emergency from a bio-juridical and biopolitical point of view, identifying two levels of problems that have arisen in dealing with the health crisis and which also constitute two lines of research. The first concerns the bioethical and bio-juridical aspect of exercising the right / duty of freedom of care; the other line of research concerns a more philosophical and biopolitical aspect of the deep meaning of the pandemic, highlighting how these two levels of argument are closely reconnected and related to each other.